An Analysis of Physics Concepts in Several Rides at Batu Night Spectacular (BNS) Indonesia - Alvian Ariantoro; Tia Rahmi Cahyani; Risqilia Ramandani; Binar Kurnia Prahani; Dwikoranto (Studies in Philosophy of Science and Education, 2021)
Edutainment can simply be defined as a learning designed by combining educational content with entertainment. This study was conducted with the aim of analyzing the physics concepts contained in several rides at the Batu Night Spectacular (BNS) amusement park. This research uses a qualitative approach and is a case study. The data collection technique used is documentation in the form of images or articles on online media. There are three rides analyzed, namely Flying Swinger, Megamix, and Gravitron. From the data and the results of the analysis that has been done, it can be concluded that, Flying Swinger, Megamix, and Gravitron work based on the concept of force or having the concept of force on them. The forces that were analyzed on the three rides were centripetal force, centrifugal force, gravitational force, frictional force, and string tension force